REVIEW FAKTOR PENENTU KEPUTUSAN INVESTASI PADA GENERASI Z & MILLENIAL - Maghfirah Nur Fadilah; Nathasya Indriwan; Nur Khoirunnisa; Sri Mulyantini (LPPM Politeknik Pratama, 2022)
Investment is one of the trends favored by various generations today, this is evidenced by the percentage growth of assets in 2021. Generation Z & Millennials are the generation that dominates the capital market in Indonesia in 2021. Knowing the behavior and factors that can affect Generation Z & Millennials in making investment decisions is the purpose of this review, so that it can be used by Generation Z & Millennials when making investments in the future. This study uses a literature review method by reviewing the behavior and investment decision factors of Generation Z & Millennials. In developed countries Generation Z & Millennials have understood the impact of investment, while in developing countries Generation Z & Millennials have a high level of trust and choose safer investment instruments. Factors that can influence investment decisions in Generation Z & Millennials include financial literacy, financial attitudes, and financial perceptions.